Penerapan Model Student Team Achievement Division dengan Media LCD Proyektor untuk Meningkatkan Motivasi Belajar Siswa Kelas VI-D pada Mata Pelajaran IPA di MIN 11 Aceh Barat - Fauzi, Ahmad; Hasnadi, Hasnadi; Irfandi, Irfandi (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study investigates the enhancement of student learning motivation through the integration of LCD projector media and the Student Teams Achievement Division (STAD) cooperative learning model in science lessons. Conducted as a Classroom Action Research (CAR), the study followed cyclical stages of planning, action, observation, and reflection. The research took place in Class VI-D of MIN 11 West Aceh during the first semester of the 2024/2025 academic year, involving 30 students (14 boys and 16 girls). Data were collected through observation, questionnaires, and documentation, and analyzed using qualitative descriptive methods. Findings indicate that (1) the use of LCD projectors combined with the STAD model was initially rated as sufficient (average score of 3.4) in Cycle I, improving to a good level (3.8) in Cycle II; (2) student motivation increased from 71.4% (moderate) in Cycle I to 92.2% (very good) in Cycle II; and (3) positive student responses rose from 59% in Cycle I to 75% in Cycle II. These results suggest that employing multimedia tools alongside cooperative learning strategies can effectively enhance motivation in science education.